Optimalisasi Rute Distribusi Paket Sekunder dalam Meminimasi Jarak Tempuh : Studi Kasus pada SPP Bandung - Adelia Suyatno; Ega Taqwali Berman; Saskia Kanisaa Puspanika (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
SPP Bandung plays a role in managing the distribution of shipments effectively and efficiently. SPP Bandung handles two types of distribution, namely primary distribution outside the Bandung area and secondary distribution to 12 distribution centers within the Bandung area. Currently, SPP operates six fleets to serve both types of distribution. However, the current distribution system has not optimized the fleet capacity, resulting in a waste of time and resources. This study uses a quantitative approach to analyze and develop an optimal distribution route strategy. By applying the saving matrix, nearest insertion, and nearest neighbor methods, the analysis results showed a decrease in total mileage from 261.8 km to 249.6 km and fuel cost efficiency from Rp210,377.33 to Rp198,539.33. The aving matrix method proved to be effective in route optimization, but other methods can also be considered for maximum improvement.